2019
DOI: 10.14221/ajte.2018v44n4.2
|View full text |Cite
|
Sign up to set email alerts
|

A Matrix of Feedback

Abstract: The present study used an established model of feedback (Hattie & Timperley, 2007) as a framework to explore which types and levels of feedback are most common in the upper primary classroom. Results demonstrate that feedback was predominantly directed toward the task level and that feed forward, information about the next steps for learning, was the least occurring feedback type in the classroom. Based upon research and findings, the authors propose a conceptual matrix of feedback that bridges research to pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 29 publications
6
57
0
4
Order By: Relevance
“…In Table 1, we report the rotated factor loadings in pattern matrices of the exploratory factor analysis output. Comparing the loading patterns with the conceptual model of feedback type and level as described in the feedback matrix (Brooks et al, 2019), we find that although these three factors do not strictly follow the three feedback types or feedback levels, they show a partially cross-classified structure of feedback types and levels. Factor 1 consists predominantly of items of feeding up and feeding back at both task and process levels, factor 2 consists of items of self-regulation level feedback, and factor 3 consists of items of feeding forward at both task and process levels.…”
Section: Exploratory Factor Analysismentioning
confidence: 90%
See 2 more Smart Citations
“…In Table 1, we report the rotated factor loadings in pattern matrices of the exploratory factor analysis output. Comparing the loading patterns with the conceptual model of feedback type and level as described in the feedback matrix (Brooks et al, 2019), we find that although these three factors do not strictly follow the three feedback types or feedback levels, they show a partially cross-classified structure of feedback types and levels. Factor 1 consists predominantly of items of feeding up and feeding back at both task and process levels, factor 2 consists of items of self-regulation level feedback, and factor 3 consists of items of feeding forward at both task and process levels.…”
Section: Exploratory Factor Analysismentioning
confidence: 90%
“…In contrast to the explicit provision of task feedback, process and self-regulatory feedback was described as being given through prompts and questions with the purpose of activating learners to engage, think, reflect, self-monitor, and act upon the feedback. Brooks et al (2019) found self-regulatory feedback occurred infrequently in the classroom. Likewise, Brookhart (2017) argues that most feedback comes from the teacher, is directed to the student and is delivered through a variety of modes.…”
Section: Self-regulation Is a Unique Feedback Levelmentioning
confidence: 96%
See 1 more Smart Citation
“…One of the most consistent findings about the power of feedback is the remarkable variability of effects. The existing research has identified several relevant moderators like timing and specificity of the goals and task complexity (Kluger and DeNisi, 1996) and sought to understand how recipients (e.g., students, teachers) receive and understand feedback, how to frame feedback to maximize this reception, and the more critical aspects of feedback that optimize its reception and use (Hattie and Clarke, 2018;Brooks et al, 2019).…”
Section: Research Questionsmentioning
confidence: 99%
“…To answer the second, third, and fourth research questions, feedback at the level of self was not included. Several authors consider self-level feedback to have a detrimental impact on learning (Brooks et al, 2019), even when it is used in combination with other feedback levels. So, after omitting the interactions with feedback moves that included self-level feedback, a total of 1,675 interactions were analysed and classified according to the different levels.…”
Section: Teacher-student Interaction: Feedback Characteristicsmentioning
confidence: 99%